ANALISIS KESALAHAN DALAM PENYELESAIAN SOAL CERITA PADA MATERI POKOK PENJUMLAHAN DAN PENGURANGAN PECAHAN PADA SISWA KELAS VIII SMP SWASTA SWADAYA KUALEU - Tefa, Kristianus; Ralmugiz, Uke; Aba, Maria Martini (MEGA: Jurnal Pendidikan Matematika, 2024)
The research method used in the form of Classroom Action Research (CAR) with data collection techniques, namely observation and test data analysis techniques, namely qualitative descriptive analysis with 19 subjects with details of 10 male students and 9 female students. This research was conducted at SMP Swadaya Kualeu with the results of the study showing that based on the description of the test results carried out on students, it can be seen the mistakes made by students in solving problems on the addition and subtraction of fractions. Through the results of data analysis, the causes of the mistakes made by students are also known. (1) Misunderstanding in the form of facts, namely Mistakes in applying plus or minus signs and brackets in algebraic forms with a percentage of 70.58 (2) Misunderstanding in the form of concepts, namely Misunderstanding the concept of like and unlike terms with a percentage of 68.62%. (3) Misunderstanding in the form of principles, namely mistakes in understanding the properties that apply to algebraic forms. (4) Errors in understanding in the form of procedures, namely, errors in understanding in completing addition and subtraction of algebraic forms, errors in understanding in completing multiplication, exponentiation of algebraic forms and division of algebraic forms. With a percentage of 72.54%